IMPLEMENTATION OF PROBLEM BASED LEARNING TO TRAIN CRITICAL THINKING SKILLS STUDENTS AT BASIC ACID MATERIALS - Reny Yulfiani; Muchlis Muchlis (JCER (Journal of Chemistry Education Research), 2021)
Abstract. This research to describe implementation of Problem Based Learning models, activities students, and critical thinking skills (CTS) in learning using PBL models on acid-base material. The design used is One Group Pretest Posttest Design with 32 subjects.  This study resulted is: (1) implementation of learning using PBL model  get the results of the average value sequentially at meetings one and two of 3.60 and 3.76, with very good criteria (2) Students perform relevant activities  meaning of students have practiced CTS. The relevant activities of students in sequence at meetings one and two of 98.75% and 97.7%. (3) CTS learners experienced an increase, overall the pretest and posttest scores of students received a percentage of 90.63% students in high category and 9.38% in medium category. The percentage of component of interpretation, inference, and analysis in high category are as follows 78.13%; 81.25%; 90.63%, and the medium category 21.88%; 18.75%; 9.28%.